BAHASA INDONESIA DALAM PERUNDANG-UNDANGAN - Wisnu Sasangka (Jurnal Sosioteknologi, 2010)
Language as a system plays an important role in expressing an idea in written and oral. The understanding of an idea would be easily done if the disclosure of the idea is laid out in orderly, neat, and concise. Similarly, Indonesian language that is used in a wide range of ideas, both in law and in other varieties will also be easily understood if expressed on a regular basis, neat, and concise. The Ease of understanding of an idea can also be done by way of recognizing, or at least know the specific characteristics of variety used it. The characteristics of a variety usually appear prominently on the use of certain lexical formation. For example, the word volcanic, tectonic,lava, and earthquakes will appear in a variety of geology, and the clinical, pharmaceutical, vaccines, additives, reproduction, sperm, and ovum will appear in a variety of medical or health; and said civil, criminal, appeal , the accused, the accused, and sanctions will arise in legal variety. In addition to lexical characteristics, other characteristics, for example, morphological characteristics and syntactical can also be used to view a certain range.